The protective effects of HMGA2 in the senescence process of bone marrow‐derived mesenchymal stromal cells. (2nd March 2020) - Yang, Ziying; Liu, Xuan; Wang, Longgang; Wang, Tao; Chen, Yueqiu; Teng, Xiaomei; Li, Jingjing; Shao, Lianbo; Hui, Jie; Ye, Wenxue; Shen, Zhenya
Abstract: Bone marrow‐derived mesenchymal stromal cells (MSCs) have been wildly applied to cell‐based strategies for tissue engineering and regenerative medicine; however, they have to undergo the senescence process and thus appeared to be less therapeutic effective. HMGA2, a protein belonged to high mobility group A (HMGA) family, exhibits an inverse expression level related to embryonic development and acts as a developmental regulator in stem cell self‐renewal progression. Therefore, we performed senescence‐associated β‐galactosidase (SA‐β‐gal) staining, transwell assay, to examine the changes of MSCs in different stages and then over‐expressed HMGA2 in MSCs by lentivirus transfection. We found the percentage of SA‐β‐gal staining positive cells in MSCs from 24‐month‐old Sprague–Dawley (SD) rats (O‐MSCs) was significantly higher compared with MSCs from 2‐week‐old SD rats (Y‐MSCs), and the expression levels of P21 and P53, two senescence‐related molecules, were also significantly up‐regulated in O‐MSCs than in Y‐MSCs. In contrast, the HMGA2 expression level in O‐MSCs was dramatically down‐regulated in contrast to Y‐MSCs. In additional, the migration ability in O‐MSCs was significantly attenuated than in Y‐MSCs. After successfully over‐expressed HMGA2 in O‐MSCs, the percentage of SA‐β‐gal staining positive cells and the expression levels of P21 and P53 were reduced, and the migration ability was improved compared with O‐MSCs without treatment. Further, mRNA sequencing analysis revealed that overexpression of HMGA2 changed the expression of genes related to cell proliferation and senescence, such as Lyz2, Pf4, Rgs2, and Mstn. Knockdown of Rgs2 in HMGA2 overexpression O‐MSCs could antagonize the protective effect of HMGA2 in the senescence process of O‐MSCs.